METODE PENGEMASAN TAUGE KACANG HIJAU MENGGUNAKAN PLASTIK POLIETILIN DAN POLIPROPILIN PADA PENYIMPANAN SUHU RENDAH - Ansar Ansar; Sukmawaty Sukmawaty; Murad Murad; Isna Hilda Arini (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2021)
Green bean sprouts are a type of vegetable that has a short shelf life. To extend the shelf life of these vegetables, they need to be stored by appropriate packaging methods. The aim of this study was to apply polyethylene (PE) and polypropylene (PP) plastic packaging to increase the shelf life of mung bean sprouts. The research was conducted by packing mung bean sprouts in PE and PP plastic at storage temperatures of 10 and 29 °C for 9 days. The parameters observed were weight loss, respiration rate, color, moisture content, and aroma. The results showed that mung bean sprouts stored in PE packaging had a longer shelf life than PP packaging. The shelf life of mung bean sprouts using PE packaging is 5 days, while PP packaging can only last 3 days at 10 °C. The shelf life of mung bean sprouts using PE packaging is 4 days, while the PP packaging can only last 2 days at 29 °C. Keywords: green bean sprouts, packaging, PE plastic, storage, temperature